Development of tuberous cassava roots under different tillage systems: Descriptive anatomy - Figueiredo, Priscila Gonzales [UNESP]; de Moraes-Dallaqua, Marina Aparecida [UNESP]; Bicudo, Silvio José [UNESP]; Tanamati, Fábio Yomei [UNESP]; Aguiar, Eduardo Barreto (Taylor & Francis, 2015)
The interaction between the roots of cassava (Manihot esculenta Crantz) and soil physical properties has previously been analyzed. This interaction results in differences in production of plant material and in the physicochemical features of the roots, suggesting that changes in soil physical conditions may be related to changes in root anatomy. This work described the anatomical development of the tuberous cassava roots (cv. IAC 576-70) under different tillage systems. Roots grown under three different tillage systems (minimum, conventional and no tillage) were examined at 15, 30, 60, 90, 120, 150 and 180 days after planting (DAP). The tillage systems did not appear to influence root anatomy during root development; at 15 and 30 DAP roots had early secondary growth; at 60 DAP the process of tuber formation had started; at 90 DAP the secondary xylem had completely differentiated to allow storage of starch; at 120, 150 and 180 DAP roots exhibited a similar anatomical structure to that observed at 90 DAP. From these results we conclude that the anatomical structure of cassava tuberous roots is established by 90 DAP and the sequence of establishment and development of tissues that make up the tuberous roots is not influenced by tillage systems during the first 180 DAP.
Keywords: Cell; Manihot esculenta Crantz; Root anatomy; Soil physical properties